Using Blogs to Teach and Promote Conservation - Sagita Mirjam Sunara (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The number of weblogs related to conservation has increased rapidly over the past few years, and are a popular tool for dissemination of conservation-related information, and raising public interest in the preservation of cultural heritage. Some student blogs are integrated into university courses on conservation, and this paper presents three such examples, illustrating how blogs can be used as a teaching and learning support tool.